Irmédi-Molnár Lászlóhoz - Lukács Károly (Fond 165 Irmédi-Molnár László, 1947)
Fond 165 Irmédi-Molnár László > Irmédi-Molnár László iratai. > Irmédi-Molnár László levelezése. > Irmédi-Molnár Lászlóhoz írott levelek.